Evaluation Website of the Bandar Lampung City Government using the Webuse Method - A Feriyanto; A Adven Tonny; Y Verawati; M S Hasibuan (Prosiding International conference on Information Technology and Business (ICITB), 2021)
The City of Bandar Lampung is a quickly creating city, to spread data and to work on great public administrations for the local area, the Bandar Lampung Regional Government has carried out a data framework e-government based site, with the location https://bandarlampungkota.go.id/ yet there are numerous objections from clients of the site which expresses that data on the difficult to come by site, reaction the site long enough when gotten to, etc, so it should be assessed convenience on site to work on the simplicity and productivity in the utilization of clients. The advancement of good-quality pages requires complex strategies for plan and assessment. One of the devices to realize the fulfillment level of a framework isthrough convenience testing. In this way, ease of use testing is led to test the fulfillment level of clients. Advancement of a Site Ease of use Assessment (Webuse)as a norm for estimating ease of use, with a-based survey assessment technique web that permits clients to survey the convenience of the site to be assessed. The site this review alludes to the Webuse to assess ease of use on the site Bandar Lampung Regional Government with the elements of Content, Organization and Readability, Navigation and Links, User Interface Design, and Performance and Effectiveness. Webuse centers around fostering an assessment framework convenience electronic with an abstract activity approach that includes the interest of clients to give an appraisal of a site. In the analysis of the usability website it can be seen that the level of usability website Bandar Lampung City Government is at point 0.74 on “good” level. The purpose of this study was to determine the level usabilityof the website Bandar Lampung City Government in service to provide optimal information and services to users. 4 elements of Webuse produce Cronbach's Alphaworth which is more noteworthy than 0.70, it tends to be deciphered that the exploration instrument utilized is truly dependable, so it is deserving of additionalexamination. Keywords—e-government, Usability, Webuse, website.